2010
DOI: 10.1287/msom.1100.0294
|View full text |Cite
|
Sign up to set email alerts
|

Do Random Errors Explain Newsvendor Behavior?

Abstract: Previous experimental work showed that newsvendors tend to order closer to mean demand than prescribed by the normative critical fractile solution. A recently proposed explanation for this mean ordering behavior assumes that the decision maker commits random choice errors, and predicts the mean ordering pattern because there is more room to err toward mean demand than away from it. Do newsvendors exhibit mean ordering simply because they make random errors? We subject this hypothesis to an empirical test that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 11 publications
7
91
0
Order By: Relevance
“…This phenomenon is called "pull-to-center" (PTC hereafter) effect. Later on, several other studies also confirmed the similar too low/too high pattern (else, underordering and over-ordering) of choices in newsvendor experiment (Benzion et al 2008, Bolton and Katok 2008, Bostian et al 2008, Lurie and Swaminathan 2009, Kremer et al 2010, Moritz et al 2013. These studies provide insights into identifying biases and decision heuristics of individual decision making in newsvendor setting.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…This phenomenon is called "pull-to-center" (PTC hereafter) effect. Later on, several other studies also confirmed the similar too low/too high pattern (else, underordering and over-ordering) of choices in newsvendor experiment (Benzion et al 2008, Bolton and Katok 2008, Bostian et al 2008, Lurie and Swaminathan 2009, Kremer et al 2010, Moritz et al 2013. These studies provide insights into identifying biases and decision heuristics of individual decision making in newsvendor setting.…”
Section: Introductionmentioning
confidence: 59%
“…For the symmetric cumulative demand function about mean, a newsvendor will exhibit "pull to center" effect Schweitzer and Cachon (2000), Bostian et al (2008), Kremer et al (2010Kremer et al ( , 2014, Bell (1982Bell ( , 1985, Sugden (1982,1987) anchoring and insufficient adjustment bias tendency of decision maker to use a reference point, or 'anchor' and then insufficiently adjusting away from this anchor two alternative anchors:  mean anchor heuristic, and,  previous demand chasing heuristic Schweitzer and Cachon (2000), Benzion et al (2008), Bolton and Katok (2008) limited rationality of decision makers due to their cognitive limitations, insufficient information, time and cost constraints a boundedly rational newsvendor chooses an order quantity which is more satisficing rather than optimal, i.e. he chooses high yielding order quantities with larger probability Simon (1955), Su (2008), Kremer et al (2010), Katok (2011), (Ovchinnikov et al 2015) overconfidenc e bias (or, overprecision) tendency of decision maker to overestimate their own opinions due to precise information that they believe they have An overconfident newsvendor will underestimate the variance of demand and make suboptimal ordering decisions.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Work examining one or two period settings or multi-period, static environments finds that individuals behave irrationally for many reasons, depending on the context, including anchoring (Schweitzer and Cachon 2000), anticipated regret (Davis, Katok and Kwasnica 2011), demand chasing (Kremer, Minner and Van Wassenhove 2010), loss aversion (Davis, Katok and Santamaría 2014), and incorrectly incorporating relevant information (Croson and Donohue 2006;Kremer, Moritz and Siemsen 2011). Once one moves to a multi-period, dynamic setting a new challenge arises.…”
Section: Discussionmentioning
confidence: 99%